Blood nickel level and its toxic effect after transcatheter closure of persistent duct arteriosus using Amplatzer duct occluder - Mulyadi M. Djer; Bambang Madiyono (Paediatrica Indonesiana, 2009)
Background  Transcatheter closure using amplatzer  duct  occluder(ADO)  is  currently the  treatment  of  choice for  patent  ductusarteriosus (PDA).  The  ADO  device  is  constructed from a Nitinolwire mesh containing 55% nickel. Up  to  now, there  is  still acontroversy about the effects  of  nickel contained in ADO.Objectives  To  determine blood nickel level  at  six months aftertranscatheter closure  of  PDA  using  ADO,  toxic effects  of  nickelat six months after  PDA  closure using  ADO,  and the effects  ofnickel  on  complete blood  count  (CBC), blood glucose and renalfunction.Methods  Subjects  were  patients  with  PDA  at  IntegratedCardiovascular Services,  Dr.  Cipto Mangunkusumo Hospital,Jakarta. Routine blood test and blood nickel levels were measuredat  the time  of  the procedure,  and  at  the  end  of  the first, third,  andsixth months after intervention.Results  There  were  29  patients who underwent heart catheteri-zation  and  PDA closure using  ADO.  A time series analysis wasconducted  on  23  patients who completed six-month follow-upafter the intervention. Median blood nickel level before procedurewas 58 ng/mL while  at  one, three  and  six months afterwards were60, 63 and 64 ng/mL respectively.  The  blood nickel levels didnot  differ significantly between pre- and  post-ADO. After  PDAclosure,  no  toxic effects  of  nickel were found,  both  clinically andlaboratorically.Conclusions  PDA  closure using  ADO  has no effects  on  the nickellevels, CBC, blood glucose and renal function;